Rice straw incorporation in a gleysol and effects on rice yield - Camargo, Flávio A. de O.; Santos, Gabriel de A.; Rossiello, Roberto O. P.; Zonta, Everaldo (Pesquisa Agropecuaria Brasileira, 1995)
With the objective of verifying the effect of rice straw on flooded rice (Oryza sativa, L.) crop production, a greenhouse experiment was carried out, using soil samples of the A and Cg horizon of gleysol from Rio de Janeiro State, Brazil. The addition of rice straw decreased total production, grain production, dry matter production of plant shoots and other production parameters. The average weight of grain was not affected by rice straw incorporation and the harvest index showed a positive response up to the level of 20 ton/ha. Production levels were higher for the superficial horizon than for the subsuperficial horizon.
Keywords: Oryza sativa; production; waterlogged soils; horizons; phytotoxity